“Estudio tecnológico para mejorar la calidad en post – cosecha del esparrago ( asparragus officinallis)” - Herrera Vásquez,Luis Enrique (1992)
The study of technological improving post-harvest of asparagus, was used as premium were controls growth of shoots at different temperatures of the soil, which confirmed that the high temperatures affect the quality of asparagus, even when it is below the Ridge (afor), producing opening of bracts of the apex of turion color changes and rapid growth. We used different temperatures (5 ° C, 10° C, 15° C and T ° amb) to study its effect on the respiratory rate and the organoleptic quality of asparagus. We found that at a temperature of 5 ° C, the respiratory rate is of only 0.07 mg CO2/g, on the fourth day. Then is the study of a new system for the preservation of the product which used styrofoam and cardboard packaging and was employed as an agent enfriante ice and ice water, as an indicator of ~ l quality was used quantity of fiber produced during the days of control p...